Encyclopedia of Aves as Supplementary Learning Material for Grade X Senior High School - Mimin Mardhiah Zural; Sisi Amanda Amanda; Nurhadi Nurhadi; Annika Maizeli (Universitas Lambung Mangkurat, 2025)
This study aims to develop Aves encyclopedia teaching materials to support the learning process on the material of classification of living things so that it can be used to help students observe and identify the types of Aves in Indonesia. This development research uses the Plomp Model with the stages of preliminary study, prototype, and assessment. the research results reported are the prototype stage. The data collection instrument is a validity, feasibility, and convenience questionnaire with answer options using a Likert Scale and processed using the percentage formula. Based on the encyclopedia development assessment, the results were found to be very valid (93,7%), and very feasible for the one to one test (82,5%) and for the small group test (92.36%). Based on the results of the encyclopedia development test on Aves material as additional teaching material for class X SMA / MA can be used in the learning process because it has met the criteria for validity, and the feasibility of using teaching materials.